"It is a constant struggle of trying to 'stick to my roots'": a narrative analysis of an immigrant's identities-in-making. Issue 3 (2nd July 2020) - Wang, Min
ABSTRACT: Informed by the theory of identity in practice, this study examined an immigrant student's (Yulia's) language learning experience. A narrative analysis of Yulia's personal stories reveals that her perceived identities as an intelligent, different, and special multilingual speaker have isolated her from her communities. She desperately tried to fit in with various groups in multiple communities of practice. Unfortunately, although she felt a sense of belonging, she became a modified version of herself. Shuttling among languages, cultures, and groups, Yulia found that her true self was invisible in any culture in which she found herself. Moreover, positioned as her parents' secretary and translator, Yulia believed that her lived experiences have shaped her as a resilient, mature, and independent immigrant who shouldered many familial responsibilities at a young age. Her reversed role as a parent deprived her of time and joy to be a child. Yulia's multilayered and complicated identities interacted with her actions and perspectives on herself and experiences as an immigrant. Findings indicate that this immigrant's self-formation in action at times matches and mismatches her self-conceptions based on her learning trajectories and unique situations. Thus, the researcher argues that linguistic competence does not necessarily facilitate community membership establishment.